Environmental Effects of Renewable and Non-Renewable Energy: Data from a Few Selected Group States - Ehsanullah, Ehsanullah; Al Mamun, Tuhin G M; Abdur, Rahim MD (International Journal of Energy Economics and Policy, 2025)
This study empirically investigates and compares the impact of renewable and nonrenewable energy on the environment for twenty countries according to their energy usage. The annual panel data duration is from 1990 to 2022. The empirical outcomes for comparative analysis are based on panel non- linear ARDL approach to examine the long-run and short-run relationship. The findings show that the impact of renewable countries is much positive and far better for the environment as compared to those countries using fossil fuel. A feasible justification for the positive impact of renewable energy on the environment is that these counties are using good energy sources and modern environmental techniques. In addition, these countries have higher income and better governance than the nonrenewable countries. Further the shock of the income level is positive in the case of renewable countries. Whereas the countries having nonrenewable energy sources have negative effects. Therefore, it is mandatory to improve the income and energy usage level of these countries to minimize pollution.